2013
DOI: 10.1177/1091581813504229
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of Refined Naphthenic Acids in a Repeated Dose/Developmental Toxicity Screening Test

Abstract: Naphthenic acids (NAs) are primarily cycloaliphatic carboxylic acids with 10 to 16 carbons. To characterize the potential of refined NAs (>70% purity) to cause reproductive and/or developmental effects, Sprague-Dawley rats (12/group) were given oral doses of 100, 300, or 900 mg/kg/d, beginning 14 days prior to mating, then an additional 14 days for males or through lactation day 3 for females (up to 53 days) in a repeated dose/reproductive toxicity test (Organization for Economic Cooperation and Development [O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Additional studies primarily addressing the aquatic toxicity of OCOCs are found in the scientific literature. These include research conducted on: 1) weathered crude oils (Wolfe et al 1995;Neff et al 2000;McGuire et al 2018), 2) crude oilproduced water (Thomas et al 2009;Scarlett et al 2012;Hughes et al 2017), 3) water-accommodated fractions (WAFs) or water-soluble fractions of fresh or artificially weathered crude oils (Barron et al 1999 [WAFs]; Melbye et al 2009 [water-soluble fractions]), 4) WAFs of refined fuels (Neff et al 2000), and 5) oil-sands process water to assess the toxicity of naphthenic acids (Rogers et al 2002;McKee et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies primarily addressing the aquatic toxicity of OCOCs are found in the scientific literature. These include research conducted on: 1) weathered crude oils (Wolfe et al 1995;Neff et al 2000;McGuire et al 2018), 2) crude oilproduced water (Thomas et al 2009;Scarlett et al 2012;Hughes et al 2017), 3) water-accommodated fractions (WAFs) or water-soluble fractions of fresh or artificially weathered crude oils (Barron et al 1999 [WAFs]; Melbye et al 2009 [water-soluble fractions]), 4) WAFs of refined fuels (Neff et al 2000), and 5) oil-sands process water to assess the toxicity of naphthenic acids (Rogers et al 2002;McKee et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report revealed that treatment of rats with refined NAs (>70% purity) at 300 and 900 mg/kg/d would cause a significant reduction in the number of live born pups. Moreover, alive pups born in the high dose group (i.e., 900 mg/kg/d) had a significantly lower body weight and decreased survival rate . However, the cause of embryonic and postnatal lethality remains to be investigated …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alive pups born in the high dose group (i.e., 900 mg/kg/d) had a significantly lower body weight and decreased survival rate . However, the cause of embryonic and postnatal lethality remains to be investigated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall no-effect levels were approximately 100 mg/kg/d. 92 It should be noted that higher molecular weight naphthenic acids, isolated from waste streams from oil sands operations, produced systemic and developmental effects at levels much lower than those tested in the present study. 93,94 Waste oils are primarily the hydrocarbon constituents collected as wastes in the refinery, particularly from sumps.…”
Section: Characterization Of Toxicological Hazard Information For Majmentioning
confidence: 80%